Changes of Soil Density and Water Content at the Treatment of Compost Media and Husk Charcoal on Lettuce Plants in the Land Degradation - Yusriani Nasution; Fitria Fitria (Postgraduate, University of Mataram, 2023)
Soil density and soil water content are physical properties that greatly affect the process of nutrient absorption in plants. This study aims to determine changes in soil density and soil water content in the treatment of compost and husk charcoal on lettuce production on degraded land. Degraded soil is soil that is low in nutrients. Thus, to increase the fertility of the soil, it is very necessary, one way is to provide compost and husk charcoal in the planting media. This study used four treatments with six replications, (M0) control (M1) compost 2.50 kg (M2) husk charcoal 2.5 kg and (M3) compost and husk charcoal 2.50 kg. Changes in soil water content and the highest was compost and husk charcoal (M3) volume 13.03 to 39.50 %, the best soil density was husk charcoal (M3) 0.66 gcm-3. The highest lettuce production was (M3) 1.32 kg. The use of compost and husk charcoal (M3) gave the best changes in soil properties and resulted in the highest production of lettuce